Analysis Implementation Extension Program Of Capture Fisheries In Indragiri Hilir Regency Riau Province - Hendri, Ridar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in January 2014 in Indragiri Hilir (Inhil), RiauProvince. This study aims to determine how the implementation of fisheriesextension program in the regency. The population in this study is the fisheriesinstructor in Inhil Regency totaling 21 people. The respondent are two fisheriesinstructors in Concong Village, District Concong, choised pusposive. Other datawere taken from the informen, which consists of the Executive Agency officialsExtension and Food Security (BP2KP) and the Department of Marine andFisheries (DKP) Indragiri Hilir. The method used in this study is a survey method.While the analysis of the data using analysis of KPI (Key Performan Indicator).The results showed that the number of fisheries instructor are 21 people, the targetis the group of fishermen, the extention system is visit, training and supervision(Lakusisi). While the extension method used is anjangsana, field schools,colloquium, workshop pulpit, open-field, business meeting, discussion opinions.Media used include extension of print media, television and radio. KPI analysisresults of the implementation of fisheries extension only reaches 48%, whichmeans less effective.Keywords: Analysis, Implementation Program, Extension of Capture Fisheries